PROPAFENONE FOR SINUS RHYTHM RECOVERY AND SUPPORT IN PATIENTS WITH PERSISTENT FORM OF AURICULAR FIBLILLATION. "PROMETHEUS" - OPENED MULTICENTER STUDY IN RUSSIAN FEDERATION - I. G. Fomina; A. I. Tarzimanova; A. V. Vetluzsky (Столичная издательская компания, 2016)
Aim. To study efficiency and safety of propafenone internally used for recovery and support of sinus rhythm in patients with the persistent form of auricular fibrillation (AF). Material and methods. 503 patients with the persistent form of AF, aged 31-68 years were included into multicenter study. Patients were randomized into 2 groups. First group included 285 patients, who were prescribed propafenone (Propanorm, PRO.MED.CS Praha a.s., Czech Republic) in a single per oral dose of 600 mg for AF paroxysm relief. Second group included 218 patients, who took propafenone for AF paroxysm prevention in daily dose of 450 mg. Efficiency of sustaining antiarrhythmic therapy was assessed in 1, 3 and 9 months after the treatment started by carrying out daily monitoring of EKG. Results. Propafenone in a single per oral dose of 600 mg leaded to sinus rhythm recovery in 230 (81%) patients. Average time for sinus rhythm recovery made up 210±50 minutes. Relief, caused by propafenone within 4 hours after taking the drug, was observed in 182 (64%) patients. Propafenone in dose of 450 mg daily lets keep sinus rhythm after 1 month of treatment in 161 patients (74%), after 3 months - in 130 patients (60%) and after 9 months - in 98 patients (45%). Effect of preventive antiarythmic therapy within first 3 months of treatment with propafenone can be regarded good, and within 9 months - satisfactory. Conclusion. Propafenone in per oral single dose of 600 mg is an efficient method of sinus rhythm recovery in patients with the persistent form of AF, and its long-term usage in dose 450 mg daily is an efficient and safe method of sinus rhythm support.